Fraksinasi Minyak Sawit Kasar dengan Pelarut Organik dalam Pembuatan Konsentrat Karotenoid - Nur Wulandari; Herher Hernawati (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2017)
Efforts to collect carotenoid components from palm oil by crystallization fractionation method with organic solvents can improve the added value of palm oil. The objective of this research was to study the process of crude palm oil fractionation with various organic solvents and find out the types of organic solvent that can produce carotenoid concentrates with high concentration and recovery, and know the effect of organic solvent treatment on the content of tocopherol in carotenoid concentrate. This study consisted of two stages, the CPO raw material characterization stage and the solvent selection phase. The solvents used were acetone, benzene, ethanol, diethyl ether, hexane, isopropanol, carbon tetrachloride, metanol, petroleum ether, and toluene. Fractionation is carried out at gradually lowered temperatures from room temperature (2 oC) to 20oC, 15oC and lower temperature. Result showed that solvents that produce high concentrations and recovery of carotenoids at stage 1 were acetone, hexane, petroleum ether, diethyl ether, benzene, and toluene. The results of stage 2 for solvent selection showed that the sample with acetone solvent had the highest carotenoid concentration but the recovery was still low at 28.58%.